Rapid and Highly Sensitive Extended Gate FET-Based Sensors for Arsenite Detection Using a Handheld Device. (12th August 2020) - Tatavarthi, Sai Sudheer; Wang, Shin-Li; Wang, Yu-Lin; Chen, Jung-Chih
Abstract : Heavy metals are very harmful to the environment and is toxic which affects the human health. Monitoring the heavy metal ion in food and water is necessary. In this research, we developed a FET based ion selective sensor for detecting Arsenite (As(III)) ions by a hand held device. The sensor characteristics are carried out and illustrated. This selective sensor shows higher sensitivity (35.19 mV/log [As 3+ ]) than the ideal Nernstian slope. The dynamic range of the Arsenite based ion sensor is from 10 −10 M to 10 −4 M. The detection limit of this FET based ion selective sensor is below 10 −10 M and is comparable to ICP-MS. The sensor captures the particular target ion and is not affected by the interfering ions such as Cadmium and Lead. The sensitivity and selectivity characteristics are comparatively better than the traditional potentiometric Ion selective electrode (ISE). The sensor has shorter response time and is easy to operate. This sensor is affordable for everyone and convenient to use for monitoring the food and drinking water frequently.